Exploratory analysis of spatial data of patients with rhino pharyngitis, asthma and bronchitis in the outpatient clinic of Santa Rosa Hospital – 2006 - Zuñiga Vilca, Carla Patricia (2019)
The objective of this work is to evaluate the type of spatial pattern followed by the cases of patients with Rhino pharyngitis, asthma and bronchitis the year 2006 in the city of Lima, who were treated by the Santa Rosa Hospital. An exploratory analysis of spatial data (AEDE) was used, obtaining as a result that the cases of asthma treated by the Hospital Santa Rosa do not present a spatial pattern throughout Metropolitan Lima (inhomogeneous distribution), being more intense in those districts more close to said hospital and specifically in the District of Pueblo Libre. In addition, the presence of significant clusters occurred in the districts of Pueblo Libre, Breña, Jesús María, Magdalena del Mar, San Miguel and Lima.